Adaptive Dissonance And Identity Reconstruction In Intra-Institutional Student Transfer: A Transcendental Phenomenological Study - Ulfi Azizia Maulana; Nurul Hidayahsyah; Qonita Rahmawati; Syarifah; Abu Darda (CV Putra Publisher, 2026)
Student transfer within the same institution represents a unique educational transition that remains underexplored in the literature on student adaptation and identity development. This study aimed to investigate the lived experiences of students undergoing intra-institutional transfer, focusing on the emergence of adaptive dissonance and the process of identity reconstruction. Employing a qualitative approach using a transcendental phenomenological design, the study involved seven purposively selected participants who had relocation between campuses within the same educational institution. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using phenomenological procedures including horizontalization, thematic clustering, textural-structural description, and synthesis of meaning. The findings revealed four interconnected themes: (1) adaptive dissonance arising from tensions between previously internalized competencies and localized institutional norms; (2) the experience of selected status as a simultaneous source of privilege, pressure, and responsibility; (3) identity reconstruction through negotiation of dual roles as senior students and newcomers; and (4) a meaning-making process that transformed emotional disorientation into personal growth and resilience. The study found that successful adaptation was rooted not merely in behavioral adjustment but in participants’ ability to reconstruct their identities and derive meaning from transitional experiences. Theoretically, the study introduces adaptive dissonance as a novel construct within educational transition research. Practically, the findings highlight the importance of institutional support systems that facilitate psychosocial adaptation, reflective learning, and identity development among internally transferred students.